Characterization of polymetallic ore and flotation concentrate from the Mária Mine (Rožňava, Špis-Gemer Ore Mts., Eastern Slovakia). Issue 1 (November 2021) - Hredzák, Slavomír; Matik, Marek; šestinová, Olga; Kupka, Daniel; Hančul'ák, Jozef; Zubrik, Anton; Znamenácková, Ingrid; Dolinská, Silvia; Sisol, Martin; Marcin, Michal
Abstract: The contribution deal with the study on composition of tetrahedrite-bearing siderite ore from Maria Mine nearby Rožnava and of tetrahedrite concentrate prepared from this ore by froth flotation. The Rožnava ors field consists of two main vein systems, namely Mária and Strieborná (Argenteous/Silvery) ones, respectively. The both vein systems are situated in the Early Paleozoic Gelnica Group of the Gemeric Superunit, in Bystrý Potok Formation (Upper Silurian) and in the Drnava Formation (Early Devonian). The filling of vein systems is formed mainly by siderite, quartz, tetrahedrite, pyrite, arsenopyrite, chalcopyrite, ankerite, albite, pyrrhotite, marcasite, less tourmaline, sericite, chlorite, apatite, magnetite, etc. The rock surroundings is represented by quartzy metapsammite, sericitic-quartzite and sericitic-graphitic phyllites (Jakubiak, 2008, Blišt'an, 2009, Varga, 2013, Mikus, 2018). Thus, metal ore as a feed to froth flotation and obtained concentrate were subjected to grain size analysis. The grain size fractions were assayed using GA, AAS, MS-ICP and CHNS. Mineral composition of samples was studied using XRD. So, polymetal ore contains 18.99 % SiO2, 37.01 % FeO, 1.84 % MnO, 7.36 % C, 2.36 % Cu, 1.70 % Sb, 0.15 % As, 2.32 % S, 770 ppm Ag and 216 ppm Hg. Tetrahedrite concentrate containing 25.59 % Cu, 19.68 % Sb, 1.19 % As, 20.08 % S, 0.57 % Ag, 1.20 % Hg, 1 % SiO2, 16.16 % FeO, 0.48 % MnO and 2.17 % C at a mass yield of 4 % was prepared. XRD study showed that siderite occurs as a dominant mineral in metal ore. Quartz, tetrahedrite and sericite are presented as accompanying minerals. Accessories are represented by chlorite, probably clinochlore. As to flotation concentrate, tetrahedrite is dominant mineral, which accompanied by siderite. Accessories can be represented by chalcopyrite, arsenopyrite, sericite, pyrite, quartz and chlorite.